Inhibition of Fungal β-1,3-Glucan Synthase and Cell Growth by HM-1 Killer Toxin Single-Chain Anti-Idiotypic Antibodies - Selvakumar, Dakshnamurthy (American Society for Microbiology, 2006)
Single-chain variable-fragment (scFv) anti-idiotypic antibodies of an HM-1 killer toxin (HM-1) from the yeast Williopsis saturnus var. mrakii IFO 0895 have been produced by recombinant DNA technology from the splenic lymphocytes of mice immunized by idiotypic vaccination with a neutralizing monoclonal antibody (nMAb-KT). The fungicidal activity of scFv anti-idiotypic antibodies against the isolates of four Candida species was assessed by MIC analysis. scFv antibodies were fungicidal at concentrations of 1.56 to 12.5 μg/ml in vitro against four Candida species. The scFv antibodies exerted a strong candidacidal activity in vitro, with 50% inhibitory concentration (IC(50)) values ranging from 7.3 × 10(−8) to 16.0 × 10(−8) M, and were neutralized by adsorption with nMAb-KT. Furthermore, all scFv antibodies effectively inhibited fungal β-1,3-glucan synthase activity in vitro, with IC(50) values ranging from 2.0 × 10(−8) to 22.7 × 10(−8) M, values which almost coincide with the values that are inhibitory to the growth of fungal cells. Binding assays showed that the scFv antibodies specifically bind to nMAb-KT, and this binding pattern was confirmed by surface plasmon resonance analysis. The binding ability was further demonstrated by the competition observed between scFv antibodies and HM-1 to bind nMAb-KT. To the best of our knowledge, this is the first study to show that an antifungal anti-idiotypic antibody, in the form of recombinant scFv, potentially inhibits β-1,3-glucan synthase activity.